2013
DOI: 10.1242/jeb.087528
|View full text |Cite
|
Sign up to set email alerts
|

On the methodological limitations of detecting oxidative stress: effects of paraquat on measures of oxidative status in greenfinches

Abstract: SUMMARYOxidative stress (OS) is widely believed to be responsible for the generation of trade-offs in evolutionary ecology by means of constraining investment into a number of components of fitness. Yet, progress in understanding the true role of OS in ecology and evolution has remained elusive. Interpretation of current findings is particularly hampered by the scarcity of experiments demonstrating which of the many available parameters of oxidative status respond most sensitively to and are relevant for measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Similar to the findings of these studies, we found that the antioxidant concentration did not change after treatment with LPS in C. perspicillata. Potentially, an antioxidant barrier needs longer than 24 h to be raised, as there may be a time lag between an increase of free radicals and the corresponding antioxidant response (Hõrak and Cohen, 2010;Meitern et al, 2013). In their study on red-legged partridges, PerezRodriguez and his colleagues (Perez-Rodriguez et al, 2008) argued that, alternatively, pro-oxidants could have been buffered by carotenoids, which they have measured separately and found to decrease after the immune challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings of these studies, we found that the antioxidant concentration did not change after treatment with LPS in C. perspicillata. Potentially, an antioxidant barrier needs longer than 24 h to be raised, as there may be a time lag between an increase of free radicals and the corresponding antioxidant response (Hõrak and Cohen, 2010;Meitern et al, 2013). In their study on red-legged partridges, PerezRodriguez and his colleagues (Perez-Rodriguez et al, 2008) argued that, alternatively, pro-oxidants could have been buffered by carotenoids, which they have measured separately and found to decrease after the immune challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, directly measuring RS production in whole organisms is not yet feasible (Cohen and McGraw, 2009;Cohen et al, 2007;Costantini and Verhulst, 2009;, although there are a variety of indirect measures of RS production that can be useful (Abuja and Albertini, 2001;Meitern et al, 2013;Miller et al, 1993;Monaghan et al, 2009). Instead, most studies examine the damage caused by RS (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Greenfinches tolerate captivity well [32], which facilitates research in ecophysiology, e.g. [33], immune function [34, 35], chronic infections [36, 37], oxidative stress [38], behaviour [39] and personality [40]. Currently there is no greenfinch gene expression data in the NCBI nucleotide database.…”
Section: Introductionmentioning
confidence: 99%